A prospective, multicentre study of external ventricular drainage-related infections in the United Kingdom and Ireland - Jamjoom, A.A.B.; Joannides, A.; Poon, M.; Chari, A.; Zaben, M.; Abdullah, M.A.H.; Roach, J.; Glancz, L.J.; Solth, A.; Duddy, J.; Brennan, P.M.; Bayston, Roger; et al. (BMJ, 2018)
Objectives